LINGKUNGAN KERJAPEMODERASI MOTIVASI KERJA TERHADAP KINERJA PERAWAT PAVILIUN EMBUN PAGI RS. DR. M. DJAMIL PADANG - Huseno, Tun (Jurnal Menara Ekonomi : Pelatihan dan Kajian Ilmiah Bidang Ekonomi, 2018)
This study aims to examine and analyze the effect of work motivation on theperformance of nurse pavilion embun pagi hospital Dr. M. Djamil Padang, test and analyze the influence of work environment on the performance of nurse pavilion embun pagi hospital Dr. M. Djamil Padang, as well as test and analyze the influence of working environment of work motivation moderator on the performance of nurse pavilion embun pagi hospital Dr. M. Djamil Padang.This research is explanatory research with quantitative approach. The sample inthe study amounted to 52 nurses pavilion embun pagi hospital Dr. M. Djamil Padang. The analytical technique used is partial least square (PLS) analysis based on variance. The result of hypothesis analysis showed that work motivation had positive and significant effect on nurse pavilion performance of embun pagi. M. Djamil Padang. Work environment has a positive and significant effect on the performance of nurse pavilion embun pagi hospital. M. Djamil Padang. Work environment has a positive and significant influence as a moderator of work motivation on the performance of nurse pavilion embunpagihospital. M. Djamil Padang .keywords: work environment, work motivation, nurse performance